Župna crkva sv. Vida s kapelom sv. Barbare u Brdovcu - novi prilozi poznavanju povijesti izgradnje i štukodekoracije - Jakaša Borić, Viki; Ožanić, Martina (2021)
U tekstu se donosi niz novih spoznaja o povijesti izgradnje i uređenja župne crkve sv. Vida u Brdovcu, koje su rezultat usporednog iščitavanja arhivskih izvora, ponajprije izvještaja kanonskih vizitacija, i nalaza konzervatorsko-restauratorskih istraživanja, a koje bitno mijenjaju prije objavljene teze. Iscrpno su sagledane sve povijesne faze s opisom građevnih transformacija i razvoja crkve, iz čega proizlazi zaključak da su se ključne intervencije dogodile tijekom 17. i 19. stoljeća, kad crkva dobiva današnji izgled. Razjašnjena je i građevna geneza kapele sv. Barbare, jedine bočne kapele kružnog tlocrta iz 17. stoljeća na području kontinentalne Hrvatske, a štukatura u njezinu interijeru, ovdje se po prvi put analizira i valorizira u kontekstu štukatura sjeverozapadne Hrvatske i susjednih regija. Prvi put se objavljuje i podatak o naručiteljici kapele i oltara sv. Barbare koju vizitatori izrijekom navode, a riječ je o Heleni pl. Patačić.
The text offers a number of new insights into the history of construction and design of the parish church of St. Vitus in Brdovec. They are the result of a comparative reading of archival sources, primarily reports of canonical visitations, and conservation and restoration research, which have significantly changed previously published theses. Rich stratification is the main feature of the church in Brdovec, and all historical phases, with detailed descriptions of renovations and the development of the church, have been thoroughly reviewed, leading to the conclusion that key interventions occurred during the 17th and 19th centuries, when the church got its present appearance. The older church, most likely from the beginning of the 16th century, was rebuilt in 1634 by extending the nave, and building a stepped bell tower in front of its western entrance. This was followed by the addition of the chapel of St. Anthony (1669) along the north wall of the nave, construction of a new wider sanctuary, and the installation of vaults over the nave which replaced the painted wooden ceiling. The construction of a new sanctuary and the "lower and upper sacristy" was arranged in 1672 with the master mason (magistrum murarium) Silvester Donati. The renovated church was consecrated in 1679; and, according to the visitor of 1686, it was under the patronage of the Čikulin family. The side chapel of St. Barbara was built between 1695 and 1700 on the site of the former masonry porch next to the south wall of the nave. The circular floor plan of the chapel is the only such example in ​​the continental Croatia of the 17th century. The dome is decorated with valuable stucco decorations that have not attracted the attention of researchers, and which, along with chapels in Zagreb and Varaždin, are the only surviving stucco from the 17th century in continental Croatia.
Bibliografske bilješke na kraju teksta ; bibliografija: str. 129-140.
Sažetak ; Summary.
Keywords: Sakralna arhitektura -- Građevinski zahvati -- Rotonda -- Štukodekoracije; Crkva sv. Vida; 17.-19. st; Brdovec